Intellectual technology in modern control systems - Mosijchuk, Natalia (My University, 2014)
The task of developing and implementing intellectual technologies in modem control objects activity is very actual and requires further development, as a number of issues still remain unresolved. Identification with fuzzy logic conclusion is one of the most effective methods for constructing models of nonlinear dependencies. Fuzzy models and algorithms for processing information allow to structure the data and to forecast the behaviour of the object in the future (for a certain period of time).
Keywords: mathematical models; control systems; intellectual technologies; математичні моделі; системи управління; інтелектуальні технології; кафедра автоматизації та комп'ютерних технологій систем управління ім. проф. А.П. Ладанюка